Physical activity and non-suicidal self-injurious behavior in Chinese adolescents: the chain mediating role of psychological capital and relative deprivation - Gao, Yingzhe; Lu, Changfen; Zhang, Xiaoqiang; Han, Beining; Hu, Huijuan (Frontiers in Psychiatry, 2024)
IntroductionPhysical activity has been shown to alleviate negative emotions. We examined whether physical activity is associated with lower non-suicidal self-injurious behavior in adolescents and the mediating and chain-mediating roles of psychological capital and relative deprivation in this association.Methods451 secondary school students (44.57% girls; ages 13-19) completed the Physical Activity Rating Scale, Adolescent Non-Suicidal Self-Injurious Behavior Scale, Psychological Capital Scale, and Adolescent Relative Deprivation Scale in their classrooms. In addition, this study used SPSS 26.0 for statistical data analysis and the SPSS macro program PROCESS 4.1 to explore the mediation role.ResultsRegression-based analyses showed that higher psychological capital and lower relative deprivation individually and sequentially mediated the association between physical activity and lower NSSI.ConclusionThese findings contribute to a deeper understanding of how and why physical activity affects adolescents’ non-suicidal self-injurious behaviors. At the same time, the result may provide new insights into prevention and intervention efforts for non-suicidal self-injurious behaviors in adolescents.